Development of Theme Based Integrated Programme with a Holistic Approach for Primary Education Curriculum - Menon, Sarala Rajan; Kadam, Seema (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Early childhood education as a basis of growth towards better future of child. In early childhood development of physical, emotional, social, ethical and moral values takes place. Child initially learns through its parents and later formal education happens in schools. In School child develop its attitude skills and knowledge based on the curriculum and pedagogy. Traditional curriculum and pedagogy are unable to develop and grow the students to face modern challenges. New Modern curriculum development or pedagogy development or text / book development will encourage improving the learning process, one of the main process of learning in this new curriculum/pedagogy /text or book development is scientific approach based learning process. The process of developing the ability to think this is a process of discovery learning as meaningful learning. Meaningful learning is needed by younger children as a learning process that will be the foundation of knowledge in the face of developmental stages of thinking that will ultimately provide a solid foundation in the face of further education stage. The learning process through a scientific approach is very appropriate if delivered through an integrated approach, thematic approach and Holistic approach. Thematic learning integrated is learning that can instill basic concepts of knowledge, to increase knowledge of facts, and can provide interesting learning because the theme is a theme that is very close to the child, simple, attractive, and incidental (according to the event is happening), Using themes while working with young children has been popular since John Dewey, an American philosopher, psychologist, and educational reformer first proposed that the curriculum should be related to real-life experiences. A thematic way to deal with instructing includes incorporating every single branch of knowledge together under one subject. Various teaching and learning methods can be used. Projects, cooperative learning, active participation, experiential learning are often highlighted. Thinking and problem solving skills, observation, critical reasoning, analysis and drawing conclusions are key skills in thematic learning Research into how the brain works and the psychology of learning shows that learning 2 is a process of integration. When we see how facts and ideas connect with one another across subjects, we are constructing meaning. When we‟re able to communicate that meaning, the learning is further reinforced. This is why theme-based learning is so effective. It‟s the most natural way to learn